Internet Addiction and Academic Performance of Students in Nigerian Universities - Adeyemi, Joseph Kayode (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Abstract The study examined internet addiction on undergraduate students’ academic performance of Adekunle Ajasin University, Akungba-Akoko in Akoko South-West Local Government Area of Ondo State., Nigeria. Five hypotheses were formulated to guide the study. Descriptive research design of survey type was adopted for the study. The sample for the study consisted of 200 respondents. A self-developed questionnaire titled “Internet Addiction and Academic Performance Questionnaire (IDAPQ) “were used to collect data from the respondents. The hypotheses were tested at 0.05 level of significance using Chi-square and t-test statistics. The findings revealed that there is a significant relationship between internet addiction and academic performance. There is significant influence of internet addiction on students’ academic performance. There is no significant influence of gender on students’ perception of the relationship between internet addiction and academic performance. There is significant influence of gender on students’ perception of the relationship between internet addiction on academic performance. There is significant influence of field of study on students’ perception of the relationship between internet addiction and academic performance. The findings further revealed that there is significant influence of the level of study on students’ perception of the relationship between internet addiction and academic performance. The findings finally revealed that there is significant influence of age on students’ perception of the relationship between internet addiction and academic performance. Based on the findings of the study, the study concluded that internet addiction influences undergraduate’s academic performance. It was therefore recommended among others that School authority should try their best their possible best in providing adequate and essential reading and writing materials needed by students in any level so that such student won’t have any excuse for his or her failure.